Efficient Herbicide Delivery through a Conjugate Gel Formulation for the Mortality of Broad Leaf Weeds - Bhardwaj, Reshu; Prakash, Om; Tiwari, Shivam; Maiti, Preeti; Ghosh, Sandipta; Singh, Ram Kumar; Maiti, Pralay (American Chemical Society, 2022)
Carfentrazone-ethyl is embedded in guar gum to prepare a polymer-herbicide conjugate gel formulation for a sustained release of the active ingredient (a.i.). The sprayable gel formulation was optimized at 0.5% (w/v) concentration. Strong interactions of the prepared composition of the polymer-herbicide conjugate system are shown through spectroscopic techniques, depicting the peak broadening of hydrophilic -OH bonds in the herbicide at 1743 cm-1, shifting to 1730 cm-1in the polymer-herbicide sample. There is a broadening and shifting of the peak at 329 nm for the n → π∗ transition at 335 nm in the polymer-herbicide conjugate system in UV spectra. Differential scanning calorimetric measurements show a lowering of endothermic melting peaks to 242 and 303 °C in the polymer-herbicide conjugate. X-ray diffraction studies showed a sharp diffraction peak of the pure polymer at a 2θ of ∼20.3°, while broadening and shifting of the peak position to a 2θ of ∼20.8° were observed after adding the herbicide. Diffusion of the active ingredient in the polymer-herbicide conjugate resulted in much greater coverage (most of the weed leaf stomata (>95%)) than conventional spraying. The efficacy of both the polymer-herbicide formulation and herbicide at different doses in weed nurseries showed significantly higher weed mortality in Anagallis arvensis (95.4%), Chenopodium album (∼97%), and Ageratum conyzoides (93.16%) treated with the polymer-herbicide formulation @ 20 g a.i. ha-1. Narrow SPAD readings range of A. arvensis (0.1-30.6) and that of C. album (0-5) were observed in the polymer-herbicide formulation @ 20 g a.i. ha-1was at par with the conventional formulation @ 30 g a.i. ha-1. Less regeneration in a weed nursery of A. arvensis (27%), C. album (77%), and A. conyzoides (49%) treated with gel formulations @ 20 g a.i. ha-1was observed, which was significantly lower than those in conventional herbicides.
This paper is submitted by the author of IIT (BHU), Varanasi, India
Keywords: Carfentrazone-ethyl; polymer-herbicide; polymer-herbicide formulation